Implementation of Musyarakah Mutanaqisah Agreement in Syariah Banking (Case Study of BTN Syariah Banda Aceh) - Rahman, Nopijal Rizki; Sitepu, Novi Indriyani; Syukri, Sarah Syukri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
MMQ is a derivative product of the Musyarakah contract and is a form of cooperation agreement between two or more parties. The DSN-MUI Implementation Guidelines No.01/DSN-MUI/X/2013 was published after the DSN-MUI Fatwa No. 73/DSN-MUI/XI/2008 is understood in various ways by various parties, causing uniformity in the implementation of Islamic financial products. This study aims to determine the implementation of the MMQ contract at BTN Syariah to analyze the suitability of the implementation of the MMQ contract with the DSN-MUI Fatwa No. 01/DSN-MUI/X/2013 and the appropriate accounting records for the MMQ contract are based on PSAK 106. This study uses a qualitative descriptive method. The results showed that the implementation of the MMQ contract at BTN Syariah was not fully in accordance with the DSN-MUI Implementation Guidelines No. 01/DSN-MUI/X/2013, the difference is that the bank does not agree to lease assets/goods to other parties and the indent provisions have not been applied, while the accounting records for the MMQ contract are in accordance with PSAK 106.